THE ROLE OF E-LEARNING IN OPTIMIZING STUDENT’S MATHEMATICS LITERATION - Amina; Gusniawati; Herlan Sanjaya (Jurnal Prinsip Pendidikan Matematika, 2021)
Changing the old pattern to a new pattern is one form of position in optimizing learning activies. Changes in this pattern, namely from teacher-centered patterns to new studen-centered patterns through the network era have a broad impact. The development of internet technology has a very big influence on learning. E-learning media makes it easier to complete activities or activities through accesing information and subject matter whenever and whereever. The method used in this study, namely using library searches and journal reviews. The use E-learning is very important in providing students to compete in this globalization era. Through E-learning media, students and meaningful learning atmosphere. Mathematical letacy skills are related to students reasoning and communication in solving a problem